PEMBERDAYAAN MATA PENCAHARIAN DI PEDESAAN MELALUI TEKNOLOGI PENETAS TELUR SEBAGAI PENDORONG PENINGKATAN EKONOMI DI DESA SIREMEN KECAMATAN TANARA KABUPATEN SERANG - Puspa, Rani; Permana, Angrian; Atoilah, Atoilah; Azizurrohim, Azizurrohim; Praditya, Dinar Okto; Ramadhan, Agung (Yayasan Education and Social Center, 2024)
This community service aims to empower livelihoods in Siremen Village, Tanara District, Serang Regency, through the application of egg hatching technology to improve the community's economy. Preliminary studies are carried out to understand village conditions, identify potential, and determine needs that form the basis for planning economic empowerment programs. Collaboration through coordination meetings with related parties, such as the village government and local breeders, has proven to be a crucial factor in the success of the program. The implementation of training and workshops focuses on increasing the knowledge and skills of village communities regarding egg hatching technology and livestock management. Research findings show that training with the active participation of local farmers can increase the acceptance and implementation of new technologies. The implementation of egg hatching technology is supported by the provision of equipment and technical guidance, increasing efficiency and productivity in its application on chicken farms. Regular monitoring and evaluation of progress on the farm, including data collection on egg and chicken meat production, is the basis for assessing the program's economic impact. Extension and dissemination of activity results through seminars, reports and scientific publications are crucial steps in increasing awareness of new technologies in the agricultural and livestock sectors. Overall, this activity succeeded in empowering livelihoods in Siremen Village, with solid collaboration, effective training, technology implementation, and regular monitoring being the key points for its success